TREATMENT STRATEGIES AND SURGICAL APPROACH FOR OBSTRUCTIVE URETERAL LITHIASIS - Laura Cristina Queiroz de Castro; Arthur Brachini Calegario; Leticia Galli de Aguiar; Ana Luíza Walter de Melo; Maria Eduarda Scheeren Xavier; Antonella Chiacchio Cagnani; Henrique Hamann Aita; Manuela Coradini Moglia; André Bolivar São Clemente; Pedro Henrique Ramos Guimaraes; Felipe Luiz Primon; Felipe Makcemiuk Dagios; et al. (International Journal of Health Management Review, 2026)
Obstructive ureteral lithiasis is a prevalent condition in urological practice, ranging from intense renal colic to severe complications such as hydronephrosis, urosepsis, and acute kidney injury, with a risk of progressive renal impairment if the obstruction is prolonged. This narrative review, based on PubMed searches using the terms "Ureteral Calculi" and "Therapeutics," discusses key emergency management strategies, ranging from conservative care to minimally invasive endourological approaches. Non-contrast computed tomography (CT) has become the diagnostic gold standard, allowing for the assessment of clinical severity and stone characteristics (size, density, and location) to determine the optimal intervention. In cases of obstruction associated with infection, immediate urinary decompression via a double-J stent or percutaneous nephrostomy is mandatory. In clinically stable patients—particularly those with distal ureteral stones up to 10 mm—medical expulsive therapy with tamsulosin yields good results. Regarding active treatment, ureterorenolithotripsy stands out due to technological advancements—such as high-power lasers, suction access sheaths, and ultra-thin flexible ureteroscopes—which enhance safety and efficacy, even in very elderly patients. In summary, the choice of therapy must be individualized, taking into account clinical severity and each patient's specific conditions to optimize outcomes and preserve renal function.